Outcome of high-risk acute myeloid leukemia after allogeneic hematopoietic cell transplantation: negative impact of abnl(17p) and −5/5q− - Middeke, Jan Moritz; Bellos, Frauke Liana; Hegenbart, Ute (Blood, 2012)
The European LeukemiaNet classification combines a heterogeneous group of aberrations as adverse-risk abnormalities. Our goal was to investigate the outcomes associated with distinct high-risk chromosomal abnormalities in acute myeloid leukemia (AML) after allogeneic hematopoietic stem cell transplantation (HSCT). We performed a retrospective cohort analysis in patients with high-risk AML who received first, HLA-compatible, allogeneic HSCT between January 2005 and December 2008. Data from 236 patients with a median age of 55 years were included. Because complex karyotype (CK), −5/5q−, and abnl(17p) are overlapping categories, a hierarchical classification system based on the presence or absence of abnl(17p) and −5/5q− was developed. Patients with abnl(17p) had a 2-year event-free survival (EFS) of 11% (95% confidence interval [CI], 0%-25%), patients with −5/5q− but no abnl(17p) a 2-year EFS of 29% (95% CI, 14%-44%), and patients with adverse-risk AML but neither of the 2 marker lesions a 2-year EFS of 49% (95% CI, 39%-59%). Notably, complex and monosomal karyotypes lost their prognostic value when these marker lesions were excluded. In conclusion, hierarchical classification of adverse-risk karyotypes by 2 marker lesions, abnl(17p) and −5/5q−, is effective in prognostication of the outcome of allogeneic HSCT in AML.
Gesehen am 29.11.2018